Law, society and corruption: lessons from the Central Asian context - Urinboyev, Rustamjon (Routledge, Taylor & Francis Group, 2025)
"This book presents new socio-legal perspectives and insights on the social life of corruption and anti-corruption in authoritarian regimes. This book takes up the case of Uzbekistan-an authoritarian regime in Central Asia and one of the most corrupt countries in the world according to Transparency International's Corruption Perceptions Index-and examines the corruption that developed in a tightly closed authoritarian regime permeated by a large-scale shadow economy, a weak rule of law, and a collectivist legal culture. Building on socio-legal frameworks of legal compliance, living law and legal pluralism, the central argument of the book is that the roles, meanings, and logics of corruption are fluid, and depend on a myriad of structural variables, and contextual and situational factors. This book will be of value to researchers, academics and students in the fields of sociology of law, legal anthropology and Central Asian studies, especially those with an interest on the intersection of law, society and corruption in authoritarian regime contexts"--